Mechanical, Tribological, and Oxidation Resistance Properties of NiCrAlY Coating by Atmospheric Plasma Spraying - Li, Bo; Ma, Shengqiang; Gao, Yimin; Li, Cong; Guo, Hongjian; Zheng, Qiaoling; Kang, Yunchuan; Jia, Junhong (Frontiers in Materials, 2019)
In this paper, the NiCrAlY coating was prepared by atmospheric plasma spraying (APS) and the influence of heat treatment on the mechanical property, tribological property and oxidation resistance property of coating were researched. The coating was heat-treated at 900 oC and 1100 oC, respectively. The microstructure of coating became more homogeneous after heat treatment. Meanwhile, heat treatment could effectively increase the microhardness and adhesive strength as well as decrease the porosity of coating. The coating presented the highest adhesive strength of 62.1 MPa and the lowest porosity of 3.06 % as well as the excellent tribological property and oxidation resistance property at 900 oC after 1100 oC heat treatment.